The value of HDL subfractions in predicting cardiovascular outcomes in untreated, diabetic patients with stable coronary artery disease: An age- and gender-matched case-control study - Zhang, Wei; Jin, Jing-Lu; Zhang, Hui-Wen; Zhu, Ya-Xin; Dong, Qian; Sun, Jing; Guo, Yuan-Lin; Dou, Ke-Fei; Xu, Rui-Xia; Li, Jian-Jun (Frontiers in Endocrinology, 2023)
Objective The aim of the present study was to examine the value of high-density lipoprotein (HDL) subfractions for predicting cardiovascular events (CVEs) in untreated type 2 diabetes mellitus (T2DM) patients with stable coronary artery disease (SCAD) using an age- and gender-matched case-control study. Methods In total, 185 SCAD patients and 185 T2DM patients with SCAD were enrolled and subjected to a clinical follow-up of CVEs. HDL subfractions were analyzed using the Quantimetrix Lipoprint System. The relationship between HDL subfractions and CVEs in T2DM patients with SCAD was evaluated by Kaplan–Meier analysis and Cox proportional hazard models. Results During a median 37.7-month follow-up, T2DM patients with SCAD had a higher percentage of CVEs compared to SCAD patients (p=0.039). The concentration of the combined intermediate and small HDL-C subfraction (defined as the mixed HDL subfraction) was related to the event incidence in T2DM patients with SCAD (p=0.004), and it was positively associated with increased CVEs even after adjustment in three models. Kaplan-Meier curve analysis indicated that T2DM patients with SCAD in the high mixed HDL subfraction group (>28 mg/dL) had lower event-free survival rates (p=0.008). Conclusions Elevated concentration of the mixed HDL subfraction predicts events in T2DM patients with SCAD.